Evaluation of patients’ knowledge and awarness of oral cavity hygiene’s influence on cardiovascular diseases - Niewęgłowska, Anna; Borkowska, Karolina; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
Introduction: Cardiovascular diseases including heart attack and stroke are the main cause of death in Poland. Out of the numerous bacteria that inhabit oral cavity, some are responsible for periodontitis. There is a confirmed correlation between chronic inflammation and cardiovascular disease. Aim of the study: The aim of study is evaluation of patients’ knowledge and awareness of the correlation between the oral health and the occurrence and development of cardiovascular diseases, especially atherosclerosis. Materials and Methods: The study included 150 patients from three locations in Lodz: Electrocardiology Clinic of Medical University of Lodz, a multi-profile clinic in Lodz and Oral Surgery Department of Medical University of Lodz. Each patient filled a questionnaire which contained demographic data (age, sex, place of residence, education), questions related to the oral cavity (a subjective estimate of the patient’s own oral hygiene, frequency of teeth brushing, last visit to the GDP), and five questions about the influence of the oral hygiene on the cardiovascular system with three options: Yes, No, and I don’t know. Results: Most patients realize that decayed teeth can cause inflammation in the body and influence the development of cardiovascular diseases. On the other hand, only less then half of the patients have knowledge about correlation between oral health and development of atherosclerosis. Conclusion: Increasing patients’ knowledge about the oral health and hygiene, the condition of the dentition and gums, and the overall health, including heart diseases, is a very important aspect of dentists’, general practitioners’ and cardiologists’ work. Patients are aware of the influence of the oral hygiene on their health but their knowledge needs to be deepened and systematized.